Epilepsy stigma and quality of life - Jacoby, Ann (Henry Stewart Talks, 2011)
Theories of stigma, ideas about epilepsy, Public attitudes to epilepsy, Rules and sanctions against people with epilepsy, Felt and enacted stigma, The issue of power, Quality of life implications of epilepsy stigma, Epilepsy as a public health problem, What can be done to reduced stigma